Progress in Cryptology - INDOCRYPT 2013 14th International Conference on Cryptology in India, Mumbai, India, December 7-10, 2013. Proceedings - Paul, Goutam.; Paul, Goutam.; Vaudenay, Paul.; Vaudenay, Paul. (Security and Cryptology ;, 2013)
This book constitutes the refereed proceedings of the 14th International Conference on Cryptology in India, INDOCRYPT 2013, held in Mumbai, India, in December 2013. The 15 revised full papers presented together with 6 short papers the abstracts of 3 invited talks were carefully reviewed and selected from 76 submissions. The papers are organized in topical sections on provable security; hash functions and signatures; side channel attacks; symmetric key cryptanalysis; key exchange and secret sharing; efficient implementation and hardware; and coding theory in cryptography.